Income distribution of general system of royalties - SGR (2016)
In Colombia there are nonrenewable resources belonging to the State, the Government offers them to get the money needed to cover the investment costs. The available those resources generated partly invested in lands where the monies were obtained and other funds are distributed among other departments. It has regulated the use thereof and in history has been discussion about the equitable distribution and control. With this writing it is disclosed simply the distribution of resources from royalties. The rule provided mechanisms for citizens to consult information General Royalties System, budgets and the execution thereof in detail and general, these data are used by the planning areas local authorities to keep track projects and to correct errors in some cases.